Effects of cadmium pollution on the safety of rice and fish in a rice-fish coculture system. (October 2020) - Luo, Wei; Wang, Dongjie; Xu, Zhou; Liao, Guoping; Chen, Defang; Huang, Xiaoli; Wang, Yan; Yang, Song; Zhao, Liulan; Huang, Huagang; Li, Yuliang; Wei, Wenyan; et al.
Graphical abstract: A model of cadmium (Cd)-contaminated RFS with the addition of 0–40 mg kg −1 Cd was simulated in the field. According to the maximum level of Cd in the grain and fish muscle of Codex Alimentarius Commission (CAC), the safety threshold of soil for Cd in the rice gain and fish muscle in a RFS was calculated to be 5.86 and 31.47 mg kg −1 . Highlights: This is the first study on the bioaccumulation of Cd in rice and fish in RFS. Fish affected the physicochemical factors of water through various activities. Soil Cd threshold for rice in RFS was higher than that in rice monoculture system. The safety risk to rice was much greater than fish in a Cd-contaminated RFS. Abstract: The rice-fish coculture system (RFS) is one of the most important and environmentally friendly agricultural systems in the world. With the increasing amounts of heavy metal contamination in the soil and water, the safe production of RFS has been greatly threatened. However, there are no reports on heavy metal uptake by rice and fish in a RFS. In this study, a model of cadmium (Cd)-contaminated RFS with the addition of 0–40.00 mg kg −1 Cd was simulated in the field. The accumulation of Cd in the rice and fish increased as the level of Cd contamination increased. Regardless of the level of contamination, the order of Cd accumulation in the rice was root > stem ≈ leaf > rice grain > brown grain and in the fish was liver ≈ gut > kidney > gill > muscle. The dissolved oxygen (DO) and the transparency of water were significantly reduced after the fish were added. The tendency of the Cd to accumulate in the fish correlated with the change of the concentration of Cd in the water ( P  < 0.05). According to the maximum level of Cd in the brown grains (0.40 mg kg −1 ) and in the fish muscle (0.10 mg kg −1 ) of Codex Alimentarius Commission (CAC), the safety threshold of soil Cd for the rice and the fish was calculated to be 5.86 mg kg −1 and 31.47 mg kg −1, respectively, indicating that the safety risk to the rice was much greater in a Cd-contaminated RFS.